How repeatable is PAPE effect: the impact of in-season isometric squat activation on countermovement jump performance enhancement in national level soccer players - Jakub Jarosz; Dawid Gawel; Pawel Grycmann; Piotr Aschenbrenner; Michal Spieszny; Michal Wilk; Michal Krzysztofik (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background The post-activation performance enhancement (PAPE) effect has been widely studied; however, its repeatability across training sessions during the competitive season in team sports has not yet been verified. Therefore, this study investigates whether PAPE effect, as measured by the countermovement jump (CMJ) without arm swing, induced by an maximum voluntary isometric squat as a conditioning activity (ICA) three days after the match, could be replicated over a 4-week training period throughout the season. The study also explores whether the magnitude of acute PAPE responses correlates with match running variables, as monitored by global positioning system (GPS) data. Methods Fifteen national level soccer players participated in the study (mean age: 26.9 ± 4.2 years, body mass: 79.2 ± 6.5 kg, height: 182.1 ± 6.5 cm, experience in soccer training: 11.2 ± 4.2 years, experience in strength training: 10.5 ± 4.6 years, relative maximal strength in squat: 1.84 kg/body mass). Each participant performed 1 repetition of the CMJ approximately 120 s before (pre-ICA) and approximately 60 s after (as post-ICA) 1 set of maximum voluntary isometric squat using a Smith machine as the ICA lasting 5 s. The measurements were repeated across 4 testing sessions performed week apart and each time 3 days after the soccer match. Moreover, running performance variables during matches including total distance, high-speed running distance, sprint distance, player load, total number of accelerations, total number of decelerations were collected via GPS system. Results A two-way repeated-measures ANOVA showed a significant main effect of time, indicating an increase in CMJ height (mean difference = 1.05 ± 0.3 cm; Cohen’s d = 0.222; p = 0.005) post-ICA compared to pre-ICA. The one-way ANOVA did not reveal significant differences between sessions, which may indicate repeatable acute PAPE responses (F = 0.093, p = 0.963, η2p = 0.006). Additionally, the one-way ANOVAs did not reveal significant differences in all GPS data between particular soccer matches (p > 0.145; for all). The interclass correlation coefficient for the PAPE response was poor to moderate (interclass correlation coefficient = 0.56, 95% confidence interval: 0.06–0.83). The Cochran’s Q test indicated that PAPE response distributions varied across sessions (p = 0.018). However, pairwise McNemar tests did not reveal significant differences (p = 0.549–1.000), suggesting that while response distribution fluctuated, no specific session-to-session differences were detected. Moreover, Pearson’s product-moment correlation coefficient, did not show significant correlation between the percentage PAPE responses and all of match GPS data variables (p > 0.074; for all). Conclusions The findings suggest that ICA can consistently elicit a PAPE response of small magnitude in national-level soccer players with a short 60-s rest interval. However, the variability in individual responsiveness and the lack of a relationship with running variables monitored via GPS during soccer matches indicate that other physiological and neuromuscular factors may influence the magnitude of PAPE responses. Given this variability, individually monitoring PAPE responsiveness may be beneficial for optimizing its application.